EU Experience Lenses: tool for evaluating and analyzing User Experience (Human Factors in Design, 2022)
The growing discussion of the User Experience resulting from the human-object interaction as a market differential brings to light the need to integrate the User Experience into the design practice of Design. Therefore, it is necessary to use appropriate tools and methodologies to consider the User Experience throughout the Design process. This article aims to present the EU Lenses of Experience and its application in a real case. The tool aims to consider the elements that make up the user experience when evaluating products, services, and digital interfaces and helps the designer in generating experience design guidelines. As a result, we obtained the presentation and application of a versatile tool for different types of projects, covering three major domains: physical product, service, and digital interface. The EU is an instrument to be integrated into the design practice of Design and is formed by three components: the Experience Reference Blocks, the Experience Mapping Canvas, and the Experience Aspects Lens.
Keywords: user experience; design practice; tool; design method; experience elements